2021
DOI: 10.21608/jntas.2021.54136.1031
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Lovastatin by Gamma Irradiated Aspergillus terreus

Abstract: is the first compound of its kind to become available for treatment of hypercholesterolemia. This fungal secondary metabolite is produced by Aspergillus, Monascus and Penicillium species, via the polyketide synthase (PKSs). The role of hypercholesterolemia as a risk factor for atherosclerosis, and ischemic heart disease was indicated by the clinical, epidemiologic and pathologic studies.In the present study, gamma irradiated of selected highly lovastatin producer Aspergillus terreus isolate (A. terreus S3γ8) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Research indicated that it could also increase the chances of getting diseases such as dementia, Alzheimer's, Ischemic heart stroke, obesity, diabetes, and certain cancers. The liver predominantly synthesizes cholesterol in a series of more than 25 enzyme-driven steps, and the rest is derived from the food we consume 1,2 . Biosynthesis of cholesterol in the body takes place through the mevalonic acid pathway.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research indicated that it could also increase the chances of getting diseases such as dementia, Alzheimer's, Ischemic heart stroke, obesity, diabetes, and certain cancers. The liver predominantly synthesizes cholesterol in a series of more than 25 enzyme-driven steps, and the rest is derived from the food we consume 1,2 . Biosynthesis of cholesterol in the body takes place through the mevalonic acid pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant enzyme targeted for controlling the cholesterol level is 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, the rate-limiting and regulatory enzyme in cholesterol biosynthesis. The group of compounds that inhibit the enzyme HMG-CoA reductase is the statin group of molecules 1,3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations